EXCISE DUTY COMPLIANCE BEHAVIOR IN MALAYSIA - Zainol Bidin; Perabavathi Sinnasamy (International Journal of Accounting, Finance and Business, 2018)
Taxation became a main of revenue in most of the developed and developing countries.However, tax non-compliance remains a serious issue around the globe. The negative impact oftax non-compliance on the economy and the evolving nature of indirect tax in Malaysia haveinduced this study. Although this phenomenon always present, but less attention is givencompared to direct taxes such as income and corporate taxes. Malaysian government wasemphasizing on strengthening its financial capacities via indirect taxes. As a result, theestablishment of raising indirect taxes revenue is needed to ensure a sustainable country’sdevelopment. However, the level of compliance among importers still not satisfied. Thus, theobjective of this study is to examine the determinants of importers excise duty compliance. Usingthe deterrence theory as the basis of this study’s framework, data were collected from 500useable excise duty offenders scattered throughout Malaysia. Results from regression analysis(partial least square) shown that penalty rate, the probability of detection and tax knowledgerevealed a positive and significant relationship with excise duty compliance. Implications andrecommendations for policy makers are discussed.